To find the remainder when X^51+51 is divided by X+1, we have to set X+1 to Zero (0), find the value of X and then substitute that value in X^51+51 to arrive atthe remainder.

So, when X+1 = 0, X = -1.

Now, putting -1 for X in X^51+51, we get:

(-1)^51 + 51, which is nothing but -1 + 51 = 50.

Therefore, when X^51 + 51 is divided by (X+1), we get the remainder as 50.

## Answers ( )

Answer:Step-by-step explanation:To find the remainder when X^51+51 is divided by X+1, we have to set X+1 to Zero (0), find the value of X and then substitute that value in X^51+51 to arrive atthe remainder.

So, when X+1 = 0, X = -1.

Now, putting -1 for X in X^51+51, we get:

(-1)^51 + 51, which is nothing but -1 + 51 = 50.

Therefore, when X^51 + 51 is divided by (X+1), we get the remainder as 50.